Entrepreneurs’ Emotional Intelligence and Sustainability of Livestock Businesses in Nigeria - Nwankwo, Cosmas Anayochukwu; Kanyangale, Macdonald Isaac (Acta Universitatis Danubius. Œconomica, 2024)
Sustainability of livestock businesses in Nigeria and beyond have attracted views of researchers, as many livestocks businesses have failed because of the inability of entrepreneurs to apply the right entrepreneurial mindset in their respective businesses. The paper examined the effect of emotional intelligence (EI) on sustainability of entrepreneur’s livestock business in Nigeria. The study utilises the quantitative research approach. The study population consist of all employers and employees of registered livestock firms in Anambra State, Nigeria, as 363 staff and employers were sampled. Multiple regression analysis was utilised to analyse the data. The research found that EI has significant effect on sustainability of livestock business. Based on the foregoing, the study recommended that to enhance the rapid attainment of organisational objectives, the organisation should establish a conducive environment that promotes the development of cognitive ability among all staff in the organisation.